Western herbal remedies for Urinary Tract infections - Sadeq Abdulridha Gatea Kaabi; Raghad Abdulatif Abdulrazaq; Khetam Habeeb Rasool; Salam Ali Khassaf (Archive of Urological Research - Peertechz Publications, 2020)
Fourteen medicinal plants native to North America and Europe traditionally used for treatment urinary tract infections (UTIs) were reviewed for their traditional uses, pharmacological activities, Active compounds responsible for its therapeutic potential, mechanism of action of its active compounds and In Vitro and In Vivo studies of its activity in treatment of UTIs. Those medicinal plants were Junipers (Juniperus spp.), Uva ursi (Arctostaphylos uva-ursi), Rosemary (Rosmarinus officinalis), Goldenrod (Solidago canadensis, S. virgaurea and S. gigantea), Common nettle (Urtica dioica), Dandelion (Taraxacum officinale), Cranberry (Vaccinium macrocarpon), Corn silk (Stigma maydis), Couch grass (Agropyrum repens). Marshmallow root (Althaea officinalis), Hosretail (Equisetum arvense), Goldenseal (Hydrastis canadensis). Buchu (Agathosma betulina and A. crenulata) and Oregon grape (Mahonia aquifolium). All of those medicinal plants found to have various pharmaceutical activities making it potent herbal remedies for UTIs in addition to various human diseases.